Effects of membrane chlorination on performance of reverse osmosis and nano-filtration membranes - Ho, Yung Lin. (2011)
Biological fouling is a perennial problem associated with membrane technology and disinfection is used to reduce the phenomenon to prolong the life span of membranes. However, chlorine has been known to be chemically aggressive towards high performance aromatic polyamide membrane. This report discussed the effects of different chlorine concentration, under constant pH and exposure time, on the physiochemical properties and performances of three commercially available reverse osmosis/ nanofiltration membranes (NF90, BW30 and NF270, FilmTec©). The reliability of the convention expressing chlorine exposure in terms of ppm.hr was also briefly discussed. The membranes were analysed using X-ray spectroscopy (XPS), attenuated total reflection-Fourier transform infrared (ATR-FTIR), contact angle, sodium chloride and polyethelyne glycols filtration test. The XPS spectra showed that the interchangeability concept of chlorine concentration and soaking time is not reliable and that amount of chlorine attachment is proportional to chlorine concentration under same exposure time. Meanwhile the FTIR spectra revealed that chlorine caused the loss of hydrogen bonding sites by observing shift and disappearance of certain peaks after chlorination. Exposed membrane presented different degree of hydrophilicity due to differences in membrane chemistry. Initial flux for the chlorinated membranes was reduced but an increasing trend was observed with filtration time. Salt rejections for both NF90 and BW30 chlorinated membranes were comparable or slightly better than the virgin except for the salt rejections of 2000 ppm × 24 hrs and NF270 chlorinated membranes that were reduced. Salt permeability for all membranes was improved after chlorination. The rejection and permeability of PEG for NF90 have the same trend as the salt but slightly lower performance. This concludes that besides physiochemical changes, chlorination has affected the membrane performance which is chlorine concentration and membrane chemistry-dependent.